Sharia Compliance Analysis of Seabank Savings Products: A Perspective Based on Fatwa DSN-MUI No. 02 of 2000 - Setiawan Bin Lahuri; Ahmad Ageng Maulana; Ain Muttaqin; Muhammad Maulana Rizki (AL-IKTISAB: Journal of Islamic Economic Law, 2026)
In the midst of rapid digital transformation in the financial sector, digital banks such as SeaBank have become popular for offering convenient and accessible services. However, despite their technological advantages, these digital banking products often lack clear alignment with sharia principles. In particular, SeaBank's savings products raise concerns regarding the use of interest-based returns, the absence of clearly defined sharia-compliant contracts (akad), and the lack of oversight from a Sharia Supervisory Board (DPS). This situation highlights a critical gap between innovation and sharia compliance. Therefore, it is essential to evaluate the extent to which SeaBank’s savings products adhere to Fatwa DSN-MUI No. 02 of 2000, which outlines specific guidelines for savings mechanisms in accordance with Islamic law, including the prohibition of riba, gharar, and maysir. This research employs a qualitative approach with a descriptive method using library research. Data were collected through a literature review of primary and secondary sources such as books, scientific journals, fatwas, and official reports related to Islamic banking and SeaBank’s savings products. The data were analyzed by examining key elements of SeaBank’s product offerings such as the types of contracts used, fund management practices, transparency, and the presence (or absence) of sharia supervisory structures. The findings show that SeaBank’s savings products are not fully compliant with DSN-MUI Fatwa No. 02 of 2000. This non-compliance is due to the use of an interest-based system contrary to sharia principles, vague contract terms, and the absence of a Sharia Supervisory Board (DPS). To enhance compliance, SeaBank should replace the interest system with a profit-sharing model, clarify contract structures, and seek certification from the DSN-MUI. This study provides recommendations for the development of sharia-compliant digital banks to support financial inclusion and strengthen the Islamic finance ecosystem in Indonesia.